Efficacy of BI 671800, an oral CRTH2 antagonist, in poorly controlled asthma as sole controller and in the presence of inhaled corticosteroid treatment. (June 2015) - Hall, Ian P.; Fowler, Andrew V.; Gupta, Abhya; Tetzlaff, Kay; Nivens, Michael C.; Sarno, Maria; Finnigan, Helen A.; Bateman, Eric D.; Rand Sutherland, E.
Abstract: The prostaglandin D2 (PGD2 ) receptor, CRTH2, plays a role in allergic airway inflammation. The efficacy of BI 671800, a CRTH2 antagonist, was assessed in 2 separate trials in patients with asthma, in either the absence or the presence of inhaled corticosteroid (ICS) therapy. In this study, BI 671800 (50, 200 or 400 mg) and fluticasone propionate (220 μg) all given twice daily (bid) were compared with bid placebo in symptomatic controller-naïve adults with asthma (Trial 1), and BI 671800 400 mg bid compared with montelukast 10 mg once daily (qd), and matching placebo bid, in patients with asthma receiving inhaled fluticasone (88 μg bid) (Trial 2). The primary endpoint in both trials was change from baseline in trough forced expiratory volume in 1 s (FEV1 ) percent predicted. After 6 weeks' treatment, adjusted mean treatment differences (SE) for the primary endpoint compared with placebo in Trial 1 were 3.08% (1.65%), 3.59% (1.60%) and 3.98% (1.64%) for BI 671800 50, 200 and 400 mg bid, respectively, and 8.62% (1.68%) for fluticasone 220 μg bid ( p = 0.0311, p = 0.0126, p = 0.0078 and p < 0.0001, respectively). In Trial 2, adjusted mean FEV1 (SE) treatment differences compared with placebo were 3.87% (1.49%) for BI 671800 400 mg bid and 2.37% (1.57%) for montelukast ( p = 0.0050 and p = 0.0657, respectively). These findings suggest that BI 671800 is associated with a small improvement in FEV1 in symptomatic controller-naïve asthma patients, and in patients on ICS.